An account of the countries adjoining to Hudson's Bay, in the north-west part of America [electronic resource] : containing a description of their lakes and rivers, the nature of the soil and climates, and their methods of commerce, &c., shewing the benefit to be made by settling colonies, and opening a trade in these parts, whereby the French will be deprived in a great measure of their traffick in furs, and the communication between Canada and Mississippi be cut off : with an abstract of Captain Middleton's Journal, and observations upon his behaviour during his voyage and since his return - Dobbs, Arthur, 1689-1765; Middleton, Christopher, d. 1770.; Fuentes, Bartolomé de, 17th cent. (London : Printed for J. Robinson ., 1744)
"The whole intented to show the great probability of a north-west passage, so long desired, and which (if discovered) would be of the highest advantage to these kingdoms." Electronic reproduction. Mode of access: Internet. 44